DRIVING BUSINESS GROWTH THROUGH GREEN INNOVATION AND SUSTAINABILITY: EVIDENCE FROM INDONESIA’SWOOD PROCESSING INDUSTRY - Erin Natasha Tobing; Gracia Ongkowijoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study’s research objective is to analyze the relationship between Green Innovation (GI), Sustainable Practices (SP), Competitive Advantage (CA), and Business Performance (BP) in Indonesia’s wood processing industry. This research utilizes a quantitative explanatory technique and Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze the hypothesis. The research population includes medium to large enterprises in Indonesia’s wood processing industry, categorized under wood sawmilling (KBLI 1610) and wood preservation (KBLI 16102). The data was obtained through an online questionnaire, utilizing a purposive sampling technique, where 100 valid data was collected. The results demonstrate that GI has a significant and positive effect on CA and BP. SP has a significant effect on CA, however SP has a nonsignificant effect on BP. However, CA partially mediates the relationship between GI and BP. CA fully mediates the relationship between SP and BP. Thus, suggesting that firms in Indonesia’s wood processing industry should integrate green innovation and sustainable practices to gain sustained competitive advantage and enhanced business performance.